Air-steam gasification of five regional lignocellulosic wastes: Exergetic evaluation. (February 2019) - Echegaray, Marcelo; García, Daniela Zalazar; Mazza, Germán; Rodriguez, Rosa
Graphical abstract: Highlights: A thermodynamic model for lignocellulosic biomass wastes was first proposed. Real conditions of conversion not completed & presence of tar & char, were considered. The model was validated carrying out CO release measurements during the gasification. Marc has highest exergetic efficiency 90%, while exocarp has the lowest value 50%. Abstract: This study presents a thermodynamic model for describing the five wastes gasification behavior with char and tar formation. Influence of variables process on the exergetic efficiency and sustainability index was considered. In order to validate, carbon monoxide release was registered and a good fit was determined. Considering the CO content in the syngas, at 850 °C, the maximum value was observed for the marc (CO mole-percentage = 17.77%) and the minimum concentration was founded for the Pistacia vera kerman 's mesocarp (CO mole-percentage = 11.37%). However, at 650 °C, the maximum CO content was observed for the Pistacia vera kerman 's exocarp (CO mole-percentage = 9.8%) and the minimum value was founded for the Pistacia vera kerman's mesocar p (CO mole-percentage = 4.28%). Marcs has the highest exergetic efficiency, and pistachio exocarp, the lowest value. Exergetic efficiency and sustainability index decrease increasing the equivalence ratio, but, increasing the temperature; these parameters augment. Higher exergetic efficiencies are obtained via air's use than air-steam mixture's use, which is attributable to the required energy to transform water into steam. Nevertheless, its influence on the exergetic efficiency and sustainability index is not very important.